Improving travellers' trust in restaurant review sites - Anaya-Sánchez, Rafael; Molinillo, Sebastián; Aguilar-Illescas, Rocío; Liébana-Cabanillas, Francisco (Emerald Insight, 2019)
Purpose This paper aims to focus on understanding how restaurant review sites generate trust among travellers and the effect of trust on the intention to visit and recommend restaurants while travelling. Design/methodology/approach The research model was assessed with data from a sample of 439 Spanish tourists using partial least squares structural equation modelling (PLS-SEM). Findings Information quality and source credibility are key for generating website trust. Website quality does not influence trust. Website trust is a key variable for explaining both intention to visit and recommend a restaurant, offline and online. Age is a significant moderator. Research limitations/implications This study expands the literature by assessing the antecedents and consequences of travellers’ trust in restaurant review sites during their trips. Practical implications Strategies are suggested for review sites, restaurants and destination managers. Originality/value This research enhances the knowledge of how consumers perceive restaurant review sites, and their behavioural intention while travelling.
Keywords: Restaurantes, cafeterías, etc.; WOM; Restaurant industry; Review sites; Intention to visit; Website trust